2017
DOI: 10.1634/theoncologist.2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutations as Predictive Biomarker for Response to Anti-EGFR Monoclonal Antibodies

Abstract: In metastatic colorectal cancer (mCRC), therapy with anti-epidermal growth factor receptor (EGFR) monoclonal antibodies cetuximab and panitumumab is indicated in absence of mutations. Cumulative evidence shows that patients with mutations, who comprise 10% of the mCRC population, do not benefit from anti-EGFR-antibody treatment. Although guidelines state that evidence for as a predictive marker is insufficient, we highlight that the quality and quantity of evidence is higher than suggested. We therefore encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…These tumors showed cell-line-specific morphological features such as vascularization and an erratic surface ( Figure 4C). The presence of KRAS and BRAF mutations in these cell lines might contribute to insensitivity to erlotinib as studies showed that patients with BRAF mutations do not benefit from anti-EGFR treatment [34]. Furthermore, in SW620, administration of axitinib led to a significant tumor growth inhibition, which might be attributed to its relatively high expression of axitinib targets FGFR1 and TNIK ( Figure 3B).…”
Section: Axitinib Erlotinib and Dasatinib Combination Therapy Inhibmentioning
confidence: 99%
“…These tumors showed cell-line-specific morphological features such as vascularization and an erratic surface ( Figure 4C). The presence of KRAS and BRAF mutations in these cell lines might contribute to insensitivity to erlotinib as studies showed that patients with BRAF mutations do not benefit from anti-EGFR treatment [34]. Furthermore, in SW620, administration of axitinib led to a significant tumor growth inhibition, which might be attributed to its relatively high expression of axitinib targets FGFR1 and TNIK ( Figure 3B).…”
Section: Axitinib Erlotinib and Dasatinib Combination Therapy Inhibmentioning
confidence: 99%
“…KRAS mutation is considered a key point for treatment decisions in oncology as it can predict resistance to monoclonal antibodies against epidermal growth factor receptor (EGFR) [48], restricting the use of these therapies to KRAS wild-type CRC patients [10]. BRAF mutations also confer resistance to anti-EGFR therapies in patients with mCRC [49,50]. Biologic treatment is predominantly administered in combination with standard chemotherapy to mCRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…While initial studies concluded that the sensitivity and specificity of BRAFV600E IHC was too low to be useful, 22 subsequent studies have reported high sensitivity (96-100%) and specificity (98-100%) [23][24][25][26][27] using automated Ventana stainers, which were used in this study. Furthermore, BRAF testing has additional predictive and prognostic utility, [28][29][30] playing a role in predicting response to both anti-epidermal growth factor receptor (EGFR) therapies 31,32 and potentially immune checkpoint inhibitors. 33 The role of MLH1 promoter methylation analysis is less clear, having not been well studied until recent years.…”
Section: Discussionmentioning
confidence: 99%